Digital Literacy: Infographics Versus Interactives - Martínez Arias, Santiago M. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
Infographics is a new type of Journalism, a new Genre, adapted to the needs, both formal and functional, of communications. Its layout is quite different depending on two media developments, static (printed or displayed on a screen, printed graphics) or dynamic (adaptation of digital media including multimedia possibilities, multimedia graphics). This is shown in several academic studies, the infographics widespread in media use and the profusion of infographics professionals. After a summary of the situation, we study the case of three Spanish Newspapers and two from the USA with graphics department, analyzing developments informative infographics into two separate ways, printed paper or static display on the screen, and in its evolution work in the digital environment. We have checked how the general public is still not properly literate to make a general consume of the digital development. This requires a rethinking of the structure of media companies as far as graphics and data journalism is concerned.